Nonmetric dental trait in human skeletal remains from Armenian Highland : phylogenetic and evolutionary implications - Khudaverdyan, Anahit Yu. (Acta Biologica Szegediensis, 2013)
Biocultural diversity of ancient Transcaucasian populations has not been studied extensively, therefore delineating some of the patterns of phenotypic variation may be useful for understanding their ongoing evolution. Dental morphological traits were employed in this study as direct indicators of biological affinities among the populations that inhabited the Transcaucasian peninsula from the Bronze Age to 20 century. Inter-group affinities were assessed by means of a principal component and cluster analysis based on trait frequencies. The samples from Armenian highland and Georgia, is identified as possessing closer affinities to the samples from Kalmykia (Pit Grave culture), Ukraine (Tripolye culture), Ural (Sintashtinskaya, Timber Grave cultures), Volga region (Pit Grave, Balanovo, Fatianovo, Potapovsky cultures), Center Asia (Gonur-Depe, Kazibaba I /Sauromatians and Late Sarmatians/), Latvia (Kiwytkalnsk), Don region (Mayackaya, Dmitrovskaya) and Lithuania (Dzemaiti). The biologically admixed group or “Mestizo” (Armenian highland: Beniamin-Vardbakh-Black Fortress I, Karmrakar) has a more complicated pattern of phenotypic relationships but from an evident European component. From an evolutionary point of view, gene flow probably is the most important factor that changed the original gene pool through Classical time (1st century BC - 3rd century AD). This group have a complex landscape of biocultural variation reflected by their different microevolutionary histories. It is, however, feasible to depict a scenario where processes of genetic mixture or replacement probably took place at different rates on a macro-regional level.